Ten years after introduction of NADC30-like strain in China: a novel chimeric porcine reproductive and respiratory syndrome vaccine candidate - Wu, Weixin; Fang, Xinyu; Jiang, Yiyao; Hu, Jiameng; Zhou, Qiongqiong; Gao, Peng; Zhang, Yongning; Ge, Xinna; Han, Jun; Guo, Xin; Zhou, Lei; Yang, Hanchun (Frontiers in Immunology, 2025)
IntroductionPorcine reproductive and respiratory syndrome (PRRS), caused by the PRRS virus (PRRSV), is an economically significant swine disease with extensive strain variation and limited heterologous protection. Modified live virus (MLV) vaccines developed by serially passaging the virus in monkey kidney cell lines have been widely used for more than 20 years. Lineage 1 virus, such as NADC30-like in China and L1C 1-4-4 strains in the United States, have gradually become the predominant strain or the dominant recombination isolate donor strain in recent years. MLVs licensed for use in the market supply low efficacy of heterologous protection ability against the NADC30-like strain, and a vaccine with improved safety and efficacy is therefore required. The method of virulence attenuation used for classical strains may not be applicable to the development of a vaccine against NADC30-like strains due to their low fidelity of replication.MethodsChimeric RvBJ-4-(ORF2-4)SX, RvBJ-4-(ORF5-6)SX, and RvBJ-4-(ORF2-6)SX were constructed by substituting minor structural proteins (GP2, GP3, and GP4), major structural proteins (GP5 and M) or both in NADC30-like CHsx1401 to classical strain backbone BJ-4. RvBJ-4-(ORF2-6)SX. Animal trials were conducted to assess the pathogenicity and protection of chimeric viruses.Results and DiscussionChimeric virus RvBJ-4-(ORF2-6)SX demonstrates a favorable balance between safety and efficacy, with limited pathogenicity and providing faster viremia clearance as well as reduced lung lesions in vaccinated/challenged pigs. A novel strategy for providing safe and effective immunological protection against NADC30-like strains has been introduced, with the potential for implementation in the field.